Systematic literature review on audio-visual multimodal input in listening comprehension - Shaojie, Tan; Abd Samad, Arshad; Ismail, Lilliati (Frontiers Media, 2022)
The purpose of this study is to discuss the effects of audiovisual input on second language acquisition (SLA) and the factors that influence the difficulty of audiovisual learning through a systematic literature review. Prior to this systematic review, in this paper, we searched papers on related topics for the past 10 years from 2012 to 2022, and found 46 journal papers that met the research criteria. They can basically represent the scholarly work in this field. The 46 studies were published in journals indexed in Google Scholar, Eric, Scopus, and Wiley Library. Databases were selected according to a set of inclusion and exclusion criteria. The following conclusions are drawn from the literature review: Audiovisual input can provide more authentic language input and more adequate and richer multimodal cultural and situational contexts, which can better promote learners' understanding of the content and stimulate learners' interest in participating in listening comprehension tasks. The influencing factors of multimodal input on listening difficulty include subtitles, video type, and the relationship between the audio and visual input.